Community-Based Local Wisdom for the Preservation of Gumuk in Jember, Indonesia - Mochamad Ainul Yaqin; Suyahmo Suyahmo; Hamdan Tri Atmaja; Puji Hardati (Universitas Negeri Semarang, 2021)
Gumuk is a special term given by the community to a hill in Jember. With a height ranging from 1 meter to 57.7 meters, the main elements of the gumuk are rock and soil. However, over time many gumuk have been exploited by local residents, especially the owners of the gumuk, which have an impact on environmental damage. Lack of public knowledge about the importance of the existence of gumuk needs to be given education for conservation based on local wisdom of the Jember community. This study aims to develop the concept of community education based on local wisdom in the preservation of gumuk in Kaliwates District, Jember. The research method that will be used is qualitative research with ethnographic and phenomenological approaches to analyze the local wisdom of the community. Data was collected by observation and in-depth interviews with several informants relevant to the research objectives. The results of the research are 1) Products, the concept of community education based on local wisdom in the preservation of gumuk, 2) a book with the title: 'Local Wisdom in preserving the gumuk.